The Effectiveness of STEM-PjBL in Enhancing Science Process Skills in Chemistry: A Focus on Stoichiometry - Anugrah, Indah Rizki (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2025)
The challenges of 21st-century education require students to develop critical thinking, creativity, and problem-solving skills. Science Process Skills (SPS) play a pivotal role in fostering scientific competence, especially in chemistry learning. This study aims to analyze the implementation and effectiveness of the STEM-Project Based Learning (STEM-PjBL) model in enhancing students’ SPS on the topic of stoichiometry. This research employed a quasi-experimental design with a pretest-posttest control group, involving 66 tenth-grade students from SMA Islam Al-Azhar 5 Cirebon, equally divided into experimental and control classes through cluster random sampling. The experimental class received instruction using the STEM-PjBL model, while the control class was taught using conventional methods. Research instruments included a validated SPS test and observation sheets. Data were analyzed using SPSS 26, including normality and homogeneity tests, independent sample t-test, and normalized gain (N-gain) calculations. The results showed that students in the experimental class demonstrated significantly greater improvement in all 11 aspects of SPS, including observing, classifying, predicting, hypothesizing, planning experiments, applying concepts, and communicating scientific findings. The t-test revealed a significant difference between the two groups (p < 0.05), while the N-gain in the experimental class (mean = 0.574) was categorized as moderate and higher than the control group (mean = 0.274). These findings indicate that the STEM-PjBL model is an effective and innovative instructional strategy for improving science process skills and conceptual understanding in chemistry education, particularly in complex topics such as stoichiometry.